Additions to the knowledge of the genus Lyroda Say (Hymenoptera: Crabronidae) from India with the descriptions of two new species - Ayisha Mawadda, N.v.; Girish Kumar, P.; Sureshan, P.m. (Zootaxa, 2021)
The species of Lyroda Say from India are examined and two new species are described: Lyroda aurea Mawadda and Girish Kumar and L. nuda Mawadda and Girish Kumar. L. binghami Tsuneki is newly reported from India. Records of other species of Lyroda from various states of India are presented. A modified key to the species of Lyroda from the Oriental Region is provided.